All-Organic Waveguide Sensor for Volatile Solvent Sensing - Nitiss, Edgars; Bundulis, Arturs; Tokmakovs, Andrejs; Busenbergs, Janis; Rutkis, Martins (Springer Verlag, 2019)
An all-organic Mach-Zehnder waveguide device for volatile solvent sensing is presented. Optical waveguide devices offer a great potential for various applications in sensing and communications due to multiple advantageous properties such as immunity to electromagnetic interference, high efficiency, and low cost and size. One of the most promising areas for applications of photonic systems would be real-time monitoring of various hazardous organic vapor concentrations harmful to human being. The optical waveguide volatile solvent sensor presented here comprises a novel organic material applied as a cladding on an SU-8 waveguide core and can be used for sensing of different vapors such as isopropanol, acetone, and water. It is shown that the reason for the chemical sensing in device is the absorption of vapor into the waveguide cladding which in turn changes the waveguide effective refractive index. The presented waveguide device has small footprint and high sensitivity of the mentioned solvent vapor, particularly that of water. The preparation steps of the device as well as the sensing characteristics are presented and discussed.
This work was supported by ERDF 1.1.1.1 Activity Project Nr. 1.1.1.1/16/A/046 “Application assessment of novel organic materials by prototyping of photonic devices”. We acknowledge Igors MIHAILOVS for valuable discussions.
Keywords: Mach-Zehnder interference; Optical sensor; organic materials; waveguide; Research Subject Categories::NATURAL SCIENCES:Physics